Persepsi Mahasiswa terhadap Pelaksanaan Perkuliahan Eksperimen Jarak Jauh Fisika Dasar di Masa Pandemi - Dina Syaflita; Naila Fauza; Zulhelmi Zulhelmi; Ernidawati Ernidawati (Universitas Indraprasta PGRI Jakarta, 2021)
The implementation of remote basic physics experiments during a pandemic has its own challenges. This experiment had problems in terms of planning, implementation, and reporting. The purpose of this study are to describe the implementation of synchronous distance learning of fundamental physics experiments using simple tools and to find out students' perceptions regarding the obstacles in the synchronous distance learning implementation of experiments. This research is a qualitative descriptive study. The instrument used is a questionnaire distributed using Google Form. The respondents in this study were 69 students who took the fundamental physics experiment course in the odd semester of the 2020/2021 academic year. Analysis of research data was carried out using descriptive analysis methods. The results of this study indicated that the application of Google Meetassisted experiments using simple tools and materials that were easily obtained by students could reduce the problem of completing tools and materials by students and the use of Google Meet allowed the mentoring process during the experiment by the lecturer. The most common obstacles encountered by students were obstacles in the implementation phase where sometimes the internet network did not support it while students needed to listen to the direction of the supporting lecturer, especially if the instructions in the manual were not well understood.